Thrombospondin-3 augments injury-induced cardiomyopathy by intracellular integrin inhibition and sarcolemmal instability - Tobias G. Schips (Nature Portfolio, 2019)
Thrombospondin 4 has been shown to protect the heart and the skeletal muscle by enhancing matrix secretion and membrane stability thanks to its intracellular function. Here the authors show that thrombospondin 3 exacerbates injury-induced cardiomyopathy and promotes destabilization of the cardiomyocyte membrane by impairing integrin trafficking to the sarcolemma.